Engineering Densely Packed Adipose Tissue via Environmentally Controlled In‐Bath 3D Bioprinting. (10th April 2022) - Ahn, Minjun; Cho, Won‐Woo; Kim, Byoung Soo; Cho, Dong‐Woo
Abstract: The adipose tissue is a crucial endocrine organ that coordinates with other organs, playing a key role in metabolic regulation. However, it remains challenging to recreate the morphology of native adipose tissue with fully packed adipogenic lipid droplets, mainly because of immature adipogenesis caused by the low cell density of current adipose constructs. This study suggests environmentally controlled in‐bath 3D bioprinting to create fully‐mature densely packed adipose tissue (DPAT) in vitro. As a bath suspension, a hybrid bioink composed of 1% alginate and 1.5% adipose‐derived decellularized matrix is developed for selective and compact cell proliferation. In the hybrid bath suspension, the construct printed at a high cell density (>10 7 cells ml −1 ) proliferates within the predefined area without unwanted cell migration throughout the bath suspension, forming a densely packed cellular microenvironment. After adipogenesis for 4 weeks, the results demonstrate that selectively proliferated preadipocytes can differentiate into lipid‐accumulating mature adipocytes. The resulting in vivo‐like DPAT is successfully engineered in vitro. The DPAT construct shows the physiological changes associated with obesity under the relevant conditions found in obese patients. The recapitulation of obesity‐induced inflamed adipose tissue through co‐culture with monocytes reveals the potency of the proposed strategy as a promising solution to overcome obesity‐related complications. Abstract : This study suggests environmentally controlled in‐bath 3D bioprinting to create fully mature densely packed adipose tissue (DPAT) in vitro. To this end, a hybrid bioink for a bath suspension and adipose tissue‐specific bioink are developed. The results demonstrate that selectively proliferated preadipocytes can form in vivo‐like DPAT. The DPAT construct also shows the physiological changes associated with obesity under the relevant conditions.